Racist discourse in the years of the Greek financial crisis: Evidence from the Greek press. Issue 1 (1st April 2019) - Lees, Christopher; Alfieris, Antonis
In the wake of Greece's economic crisis, expressions and acts of racism have become noticeably more prevalent, particularly in light of the rise of the neo-Nazi Golden Dawn party. Two significant topics in public discourse that gave rise to expressions of racism were the amendment of the Greek citizenship law, which came into effect in 2010 and was heavily debated in the run up to the 2012 Greek general elections, as well as the perceived increase in immigration at the start of the refugee crisis. By investigating newspaper articles from Greek newspapers of different political affiliations during the period around the Greek general elections of 2012, we intend to provide examples of how racism was constructed in the language of the press at the time and analyse this against the background of the economic crisis in Greece.